Knowledge and attitudes on sexually transmitted infections and HIV among undergraduates in the state universities - Upuli Amaranganie Pushpakumari Perera; Chrishantha Abeysena (Intelektual Pustaka Media Utama, 2020)
This study aimed to describe knowledge and attitudes on sexually transmitted infections (STI) and HIV among undergraduates in state universities of Western province, Sri Lanka. A descriptive cross-sectional study was conducted among second and third year undergraduates in 2014. The stratified cluster sampling method was applied to select 1575 undergraduates. A pre-tested self-administered questionnaire was administered to assess knowledge and attitudes on STI and HIV. The associations of knowledge and attitude categories with selected variables were assessed. Most (42.3%, n=667) of the undergraduates belonged to poor knowledge category, 41% (n=646) satisfactory knowledge on STI. Only 16.6% (n=262) had good overall knowledge on STI. Undergraduates who had studied in bioscience stream (36.7%, n=91) were better knowledge than others (12.6%, n=171) (p<0.001). A majority (62.6%, n=976) of undergraduates had overall good knowledge on HIV, 27.7%, (n=432) satisfactory knowledge and 9.7% (n=151) had poor knowledge. Males who had studied in bioscience stream and those who had studied at non-mixed schools were better knowledge on HIV than the counterparts. A majority (56.5%, n=883) of undergraduates had undesirable attitudes and 43.5% (n=681) had desirable attitudes towards HIV. Males (45.9%, n=294) had more desirable attitudes than females (42%, n=386) (p>0.05). Knowledge on STI was low and HIV was higher. About half of the undergraduates had desirable attitudes towards HIV.